Phenomenological Reading of the Colors of a Persian Painting from the book of Samak Ayyar of Al-Injou’s Period by Relying on the Theories of Najmuddin Kubra - Fatemeh Mehrabi (مجله مطالعات ایرانی, 2022)
Introduction